High time-resolution and time-integrated measurements of particulate metals and elements in an environmental justice community within the Los Angeles Basin: Spatio-temporal trends and source apportionment. (October 2020) - Hasheminassab, Sina; Sowlat, Mohammad H.; Pakbin, Payam; Katzenstein, Aaron; Low, Jason; Polidori, Andrea
Abstract: The Los Angeles Basin is home to several environmental justice communities that are disproportionately impacted by localized sources of air pollution. City of Paramount, CA, is one of these communities that encompasses several industrial facilities, including metal-processing and finishing companies, in close proximity to each other as well as to residential neighborhoods and sensitive receptors (e.g., schools and hospitals). Between 2016 and 2019, the South Coast Air Quality Management District conducted an extensive air monitoring campaign in this community to identify and address sources of airborne particulate hexavalent chromium (Cr (VI)) and other toxic metals. Using portable air samplers, 24-hr time-integrated total suspended particulate (TSP) samples were collected every third or sixth day at a total of 49 different locations (including 12 local schools) throughout the city for Cr (VI) analysis. In certain areas, elevated levels of Cr (VI) were initially found; consequently, additional efforts were made to better characterize sources of Cr (VI) and other metals. As part of these efforts, hourly concentrations of 20 metals were also measured continuously over 1.5 years with Xact 625 (Cooper Environmental Services, OR, USA) at two locations within the community. Air monitoring results indicated a substantial reduction in ambient levels of Cr (VI) over time as a result of enforcement actions, rule developments, and voluntary emissions mitigations. Long-term continuous multi-metals measurements provided previously unknown information on the temporal trends of metals and elements, including their diurnal, day-of-the-week, and seasonal variations. The high time-resolution measurements also enabled investigating the impact of exceptional events (e.g., 4th of July fireworks) on the levels of ambient TSP-bound metals. A Positive Matrix Factorization (PMF) source apportionment analysis on the continuous multi-metals data identified five major sources, two of which were associated with the nearby industrial emissions (together accounting for 9.8%–13.8% of total metals concentrations), while the other three were linked with resuspended soil (48.8%–69.8%), brake wear (7.3%–19.1%), and road dust (13.1%–18.3%), all with distinct profiles and temporal variations. Results from this study show how a strategic air monitoring can lead to the discovery of emission sources, and how concurrent inspection and enforcement actions along with voluntary control measures by facilities can result in substantial emission reductions. Highly time-resolved source apportionment results coupled with wind data also provide valuable information on the dynamic variation in source activity and allowed for the identification of the most probable source locations that led to elevated concentrations at the receptor sites. Highlights: An air monitoring campaign was conducted in an environmental justice community. Time-integrated and time-resolved concentrations of metals were measured. Levels of metals showed strong intra-community spatial and temporal variations. A PMF model was used to identify and quantify major sources of metals. Five major sources with distinct profiles and temporal trends were identified.